Utilising organic-mineral fertilisers produced from man-madewaste of poultry farms - Tymchuk, Ivan; Kanda, Maria; Malovanyy, Myroslav (Lviv Politechnic Publishing House, 2019)
This research is devoted to ecological problems associated with the development of poultry farming in Ukraine. It provides practical approach to the reduction of ammonium emissions from poultry farms, which results in an opportunity to produce organicmineral fertiliser. Organic-mineral fertilisers obtained this way were tested in field.
Keywords: poultry farms; man-made waste; organicmineral fertilisers; field tests